Whitewashing Slavery: Legacy of Slavery and White Social Outcomes. (25th June 2019) - Reece, Robert L
Abstract: Legacy of slavery research has branched out into an important new niche in social science research by making empirical connections between the trans-Atlantic slave trade and contemporary social outcomes. However, the vast majority of this research examines black-white inequality or black disadvantage without devoting corresponding attention to the other side of inequality: white advantage. This study expands the legacy of slavery conversation by exploring whether white populations accrue long-term benefits from slave labor. Specifically, I deploy historical understandings of racial boundary formation and theories of durable inequality to argue that white populations in places that relied more heavily on slave labor should experience better social and economic outcomes than white population in places that relied less on slave labor. I test this argument using OLS regression and county-level data from the 1860 United States Census, the 2010–2014 American Community Survey (ACS), and the 2014 United States Department of Agriculture Economic Research Service (USDA ERS). The results support my hypothesis. Historical reliance on slave labor predicts better white outcomes on five of six metrics. I discuss the implications of these findings for race, slavery, whiteness studies, and reparations.